Tubular subdermal flap to dorsal nasal reconstruction in a dolichocephalic dog: Case report - Mascella, Vivian; Gallina, Marina Frazatti [UNESP]; Dos Santos, Larissa; Dos Santos Brilhante, Natalia; Martin, Paulo Roberto; Santos, Ivan Felismino Charas [UNESP] (Editora da Universidade Federal Rural do Semi-Arido - EdUFERSA, 2021)
This case report described the use of tubular subdermal flap to dorsal nasal reconstruction of an old dolichocephalic dog. A nine-year-old Dachshund female dog-weighing 10 kg presented with deep and extensive wound in the dorsal nasal region was attended at veterinary clinic, Sorocaba city, São Paulo, Brazil. The reconstructive surgical procedure was performed in three stages with an interval time of 25 days, which included the preparation of the tubular subdermal flap; the advance of the flap to the region of the tissue defect, and the removal of excess flap. The region healed 14 days after the last stage. The tubular subdermal flap was effective for treating ulcerative epithelial wounds associated with interstitial lymphoplasmocyte dermatitis and vasculitis of the dorsal nasal region of an old Dachshund dog.
Retalho tubular subdérmico para reconstrução dorsal nasal em cão dolicocefálico: Relato de caso
Keywords: Healing; Nose; Reconstructive surgery; Skin; Wound